An observational study to assess the knowledge and attitude of medical students regarding hand washing - Saxena, Shashi; Mishra, Saurabh; Khan, Huma (International Journal Of Community Medicine And Public Health, 2019)
Background: Hand hygiene is a milestone in the field of infectious disease control. Promotion of improved hand hygiene has been recognized as an important public health measure. Therefore hand washing is being promoted in various ways. This study has been conducted to assess the level of knowledge and attitude regarding hand hygiene practices amongst the medical students to identify areas of gaps in their knowledge, attitude and practices. Methods: This is a cross sectional study conducted among medical undergraduates of a private medical college in western Utter Pradesh. A pre tested questionnaire with multiple choice questions was used for collection of data. Results: A total of 246 MBBS students participated in the study out of which 50.4 % students were male and rest were female. 78.5% participants were belonging to the age group 19-21 years. Students have good knowledge of hand washing irrespective of their educational front. Conclusions: The results of our study are fairly good still a proper training program is required to generate awareness among the community. Maintenance of hand hygiene should be a part of our education system at primary level.